Neuron density is decreased in the prefrontal cortex in Williams syndrome. Issue 1 (13th August 2016) - Lew, Caroline Horton; Brown, Chelsea; Bellugi, Ursula; Semendeferi, Katerina
Abstract : Williams Syndrome (WS) is a rare neurodevelopmental disorder associated with a hemideletion in chromosome 7, which manifests a distinct behavioral phenotype characterized by a hyperaffiliative social drive, in striking contrast to the social avoidance behaviors that are common in Autism Spectrum Disorder (ASD). MRI studies have observed structural and functional abnormalities in WS cortex, including the prefrontal cortex (PFC), a region implicated in social cognition. This study utilizes the Bellugi Williams Syndrome Brain Collection, a unique resource that comprises the largest WS postmortem brain collection in existence, and is the first to quantitatively examine WS PFC cytoarchitecture. We measured neuron density in layers II/III and V/VI of five cortical areas: PFC areas BA 10 and BA 11, primary motor BA 4, primary somatosensory BA 3, and visual area BA 18 in six matched pairs of WS and typically developing (TD) controls. Neuron density in PFC was lower in WS relative to TD, with layers V/VI demonstrating the largest decrease in density, reaching statistical significance in BA 10. In contrast, BA 3 and BA 18 demonstrated a higher density in WS compared to TD, although this difference was not statistically significant. Neuron density in BA 4 was similar in WS and TD. While other cortical areas were altered in WS, prefrontal areas appeared to be most affected. Neuron density is also altered in the PFC of individuals with ASD. Together these findings suggest that the PFC is targeted in neurodevelopmental disorders associated with sociobehavioral alterations. Autism Res 2017, 10: 99–112 . © 2016 International Society for Autism Research, Wiley Periodicals, Inc.